Gourmets in the Land of Famine : the Culture and Politics of Rice in Modern Canton. - Lee, Seung-Joon (Stanford University Press, 2010)
This book project is a cultural history of rice consumption in the city of Canton (now Guangzhou), China's southernmost metropolis. Special emphasis is placed on the qualitative dimension of the local food culture and the dynamic interactions between the local society and the modern state.